A rare side effect of methotrexate therapy: drug-induced osteopathy with multiple fractures of the lower limb. Issue 1 (21st February 2023) - Singh, Delila; Hesse, Nina; Skapenko, Alla; Schulze-Koops, Hendrik
Abstract : Methotrexate is associated with bone lesions that are rare and, although presenting with a typical localisation to the lower extremities and appearing with a characteristic radiologic morphology, largely unknown and often misdiagnosed as osteoporotic insufficiency fractures. The correct and early diagnosis, however, is key for treatment and prevention of further osteopathology. Here, we present a patient with rheumatoid arthritis who developed multiple painful insufficiency fractures in the left foot (processus anterior calcanei, tuber calcanei) and in the right lower leg and foot (anterior and dorsal calcaneus and at the cuboid and distal tibia) during therapy with methotrexate, which were all misdiagnosed as osteoporotic. The fractures occurred between 8 months and 35 months after starting methotrexate. Discontinuation of methotrexate resulted in rapid pain relief and no further fractures have occurred. This case powerfully demonstrates the importance of raising awareness of methotrexate osteopathy in order to take appropriate therapeutic measures, including and perniciously discontinuing methotrexate.